Perception of HIV-positive patients from a referral center for health care - Garbin, Cléa A.S.; Martins, Ronald Jefferson; Garbin, Artênio José Í.; Lima, Daniela C. de; Prieto, Annelise Katrine C. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: health professionals, in many cases, have defensive and exclusionary practices, patterns of prejudice and discrimination in response to HIV positive patients. Objective: to verify the perception of patients seropositives from a reference center for STD/HIV/aids in relation to health care. Methods: there were interviews with questions related to discriminatory attitudes suffered, access and health care. Results: 130 individuals participated in the survey, from which 30 (23.1%) reported events of discrimination suffered outside the center of reference, predominantly from surgeon-dentists and 112 (86.2%) believed to have the same access and health care as other citizens. 62 (47.7%) treated with the dental center of reference, of which 56 (90.3%) felt good being treated in a dental unit only for HIV positive and six (9.7%) were indifferent, believed to be more exposed, or have a bias to attend dental seropositive individuals. Conclusion: it is concluded that many patients have already been discriminated against outside the reference center. However, most of them have a positive feeling towards the treatment received at a specific place for treating HIV-positive patients, due to the feeling of being welcome at that place due to the humanization and access to health care.